Usefulness of Cytokeratin Fragment Antigen 21-1 Estimation in Fine-Needle Aspiration Washout Specimens in Diagnosis of Axillary Breast Cancer Metastasis. - Jadli, Mohit; Shirsath, Gaurav Rajendra; Gupta, Akanksha; Ahsan, Erna; Huda, Farhanul; Chowdhury, Nilotpal (Journal of Cytology)
Introduction: Fine-needle aspiration biopsy (FNAB) is a valuable technique for diagnosing axillary breast cancer metastasis. However, its sensitivity can sometimes be affected by sampling errors and technical artifacts. Aim: We examined whether cytokeratin fragment antigen 21-1 (CYFRA) estimation by manual enzyme-linked immunosorbent assay (ELISA) on FNAB needle washouts could add diagnostic information to FNAB. Materials and Methods: This cross-sectional study involved FNAB from 138 lymph nodes in 108 suspected breast cancer patients. Papanicolaou and May–Grünwald–Giemsa smears were prepared for cytological examination. CYFRA was estimated by manual ELISA from fine-needle washouts after smear preparation. A cut-off of 1.93 ng/mL was considered to be a positive test for CYFRA. Results: The CYFRA estimates were significantly associated with the FNAB results (P < 0.001 by Kruskal–Wallis test). On FNAB, 84, 5, 36, and 13 cases were classified as malignant, suspicious, benign, and inadequate, respectively. CYFRA was reported as positive in 92 cases (75 in malignant FNAB, 3 in suspicious FNAB, 11 in benign FNAB, and 3 in inadequate FNAB). Six of 11 CYFRA positives in benign FNAB were confirmed by re-examination of cytology slides; the remaining 5 CYFRA-positive cases did not have further biopsy. Only two inadequate FNAB had histopathology follow-up; both revealed metastasis, of which one was CYFRA positive. Sensitivity and specificity with 95% confidence intervals of CYFRA for detecting axillary metastasis were 0.876 [0.794, 0.934] and 0.833 [0.653, 0.954], respectively. Conclusion: CYFRA estimation by manual ELISA is a simple and accurate test which supplements and enhances the diagnostic usefulness of axillary FNAB in suspected breast cancer metastasis.